Conventional and molecular breeding strategies for improvement of drought tolerance cultivars in rice: Recent approaches and outlooks - Madhu Banoth; Umil Singh Nunavath; Sukrutha Bhimireddy; Deepika Konne; Ananda Lekshmi L; Venkateswarao Govada; Sampath Lavudya (Environment Conservation Journal, 2023)
Rice is a vital staple food, especially in Asia, but it is highly susceptible to drought, leading to significant yield losses. To ensure food sustainability, drought-tolerant rice varieties are essential. Conventional breeding methods improve drought tolerance by focusing on biometric traits like root depth, avoidance, escape, and tolerance. This involves screening and crossing drought-tolerant varieties with high-yielding ones, followed by selection and evaluation. Techniques such as pedigree selection, recurrent selection, and backcrossing introduce desirable genes to enhance drought tolerance. Induced mutation through radiation exposure is also used. The molecular basis of drought tolerance involves identifying and manipulating genes responsible for rice's response to water stress. Techniques like QTL analysis, transcriptomics, genomics, and proteomics identify genes and QTLs associated with drought tolerance. Important genes involved in drought response include DREB, LEA, and ROS scavenging genes. Identifying QTLs enables the development of molecular markers for efficient screening of drought-tolerant rice genotypes. In conclusion, conventional breeding and molecular approaches are employed to develop drought-tolerant rice varieties. Conventional breeding improves biometric traits, while molecular techniques identify and manipulate specific genes associated with drought tolerance. This combination holds promise for high-yielding and drought-tolerant rice cultivars, contributing to global food security. However, further research is needed to understand the complex genetic mechanisms underlying drought tolerance in rice and enhance breeding precision and efficiency.